Penerapan Sanksi Pidana Terhadap Pelaku Pencemaran Lingkungan di Provinsi Riau - Sanjaya, Muhammad Rio (Indra Institute Research & Publication, 2024)
Environmental damage due to environmental pollution does not only occur in Riau Province but also occurs throughout the world. So based on this, the author is interested in conducting research using library research methods, where the sources used in this writing come from books, online newspapers, previous journals, articles and documents. The formulation of the problem in this writing is (1) what is meant by environmental pollution and its scope, (2) how to apply criminal sanctions for perpetrators of environmental pollution in Riau province, (3) what obstacles are faced by the Riau Provincial government in overcoming the problem of environmental pollution and (4) what efforts are being made by the Riau Provincial government in dealing with this environmental pollution. And the conclusions are (1) environmental pollution is contamination of physical and biological components of the earth system and atmosphere in such a way that disrupts environmental processes, (2) criminal sanctions for perpetrators of environmental pollution based on Article 60 in conjunction with Article 104 The PPLH law requires a maximum prison sentence of three years and a maximum fine of three billion rupiah. And in the process of implementing criminal sanctions for perpetrators of environmental pollution in Riau Province, law enforcement officials have handled it firmly, this has been proven by the arrest of two suspects in cases of environmental pollution committed by PT. SIPP is located in Pematang Pudu Village, Mandau District, Bengkalis Regency, Riau Province. (3) The obstacles faced by the Riau Provincial government in overcoming the problem of environmental pollution are due to several influencing factors, namely inconsistent legal facilities, law enforcers who lack knowledge and understanding of the environment, a lack of sophisticated technological tools and experienced experts and lack of public awareness. (4) The government's efforts to overcome environmental pollution are by conducting outreach to the public about the importance of protecting the environment, managing peat ecosystems in a sustainable manner, carrying out waste recycling processes and making appeals to industrial owners to reduce water so that there is not a lot of waste generated. wasted.